2013
DOI: 10.4047/jap.2013.5.3.287
|View full text |Cite
|
Sign up to set email alerts
|

Peel strength of denture liner to PMMA and polyamide: laser versus air-abrasion

Abstract: PURPOSEThis study investigated the effect of laser parameters and air-abrasion on the peel strength of silicon-based soft denture liner to different denture resins.MATERIALS AND METHODSSpecimens (N=180) were prepared out of three different denture base resins (Rodex, cross-linked denture base acrylic resin; Paladent, heat-cured acrylic resin; Deflex, Polyamide resin) (75 mm × 25 mm × 3 mm). A silicon-based soft denture liner (Molloplast B) was applied to the denture resins after the following conditioning meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
15
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 42 publications
(133 reference statements)
4
15
0
1
Order By: Relevance
“…Nevertheless, limited and inconsistent findings are available regarding the effectiveness of laser treatment in improving bond strength between soft lining materials and denture resin. 11,14,17,21 In the oral cavity, liner denture base resin interface is frequently subjected to thermal stresses. It has been found that the bonding between resilient liner materials and denture resin is affected by aging in water and thermocycling.…”
Section: Jcdpmentioning
confidence: 99%
“…Nevertheless, limited and inconsistent findings are available regarding the effectiveness of laser treatment in improving bond strength between soft lining materials and denture resin. 11,14,17,21 In the oral cavity, liner denture base resin interface is frequently subjected to thermal stresses. It has been found that the bonding between resilient liner materials and denture resin is affected by aging in water and thermocycling.…”
Section: Jcdpmentioning
confidence: 99%
“…Akin et al reported that sandblasting and laser increased bond strength of silicone‐based resilient lining material. Korkmaz et al applied peel test and Usumez et al applied tensile test, and reported that laser was more effective than sandblasting and control. The number of studies applying sandblasting was also high; however, it was ineffective in increasing the bond strength.…”
Section: Discussionmentioning
confidence: 99%
“…To provide a good bond strength between the denture base resin and the resilient lining material, several investigators have used sandblasting with alumina, laser application, chemical cauterization or primers, acrylic drills or mesh textured glass fibers . This study aims to analyze published information on the bond strength of resilient lining materials applied with different surface treatments to denture base resins and using various laboratory tests.…”
mentioning
confidence: 99%
“…There are not enough investigation about the bond strength of polyamide denture and soft lining materials. Korkmaz et al 40 have found that, air abrasion of polyamide resins should be avoided not to impair their peel bond strengths to silicon-based soft denture liners.…”
Section: Discussionmentioning
confidence: 99%